Cognitive Biases in Strategic Decision-Making - Kenneth Midtgård; Marcus Selart (Administrative Sciences, 2025)
This article examines to what degree organizations use strategies that focus on maximizing shareholder value (Theory E) as opposed to strategies emphasizing the development of organizational capability (Theory O). Our main goal is to investigate the extent to which cognitive biases influenced strategic decision-making pertaining to organizational change. Strategic decision-making and organizational change both have a great impact on collaborative behavior. A survey was developed that measured different aspects of the cognitive perspective in strategic decision-making. It was distributed to managers of several medium-sized organizations in Scandinavia (n = 119). The results indicate that managers used mixed strategies (Theory E and O). The results also reveal that illusions of control together with beliefs about change processes skewed the application of strategies towards Theory E. The theoretical and practical implications of the results were finally discussed, expanding the cognitive perspective in strategic decision-making.